有限元方法在大高宽比微型齿轮强度分析中的应用 - 周春国; 刘凯; 李彦平; 蒋庄德 (Jixie chuandong)
The paper researches the finite element method of strength analysis of micro-gear with large ratio between height and width. From the practical using of micro-machine, based on establishing the micro-gear’s three dimension model, the boundary condition and mesh dividing are completed. The tooth root stress of micro-gear is processed with the software of the finite element analysis. It is helpful for micro-gear designing.